Sistem Informasi Geografis Peternakan Ayam Pada Kabupaten Jembrana Berbasis Website - Fatmasari, Ni Made Mila; Swastika, I Putu Agus; Utami, Nengah Widya (Universitas Pendidikan Ganesha, 2021)
This thesis proposal discusses the difficulties of chicken buyers to get information on chicken farms in Jembrana Bali, and the limited information obtained, currently complete information on farm layout in Jembrana Regency, only exists at the Jembrana District Animal Husbandry Service, then chicken breeders are also it is still difficult to provide information about their layout due to the limited means of adequate information in each village. So a chicken farm geographic information system was created with the aim of helping chicken buyers, livestock raisers and the Chicken Farming Service to get information on chicken breeding in Jembrana Regency more easily.Keywords— livestock, chicken, GIS, Website, Jembrana